2019
DOI: 10.1021/acs.orglett.9b02336
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Selective Oxidative (Spiro)annulation of 2-Arylindoles by Using Benzoquinone as a C2 or C1 Synthon

Abstract: Rhodium-catalyzed substrate-tunable oxidative annulation and spiroannulation reactions of 2-arylindoles with benzoquinone leading to 9H-dibenzo­[a,c]­carbazol-3-ols and new spirocyclic products are reported. Intriguingly, with 2-aryl-substituted indoles, benzoquinone could act as a C2 synthon to afford dibenzo­[a,c]­carbazoles. On the contrary, when 2-aryl-3-substituted indoles were used, benzoquinone switched to act as a C1 synthon to furnish spirocyclic compounds. In addition, further transformations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Guo et al . reported a indole‐directed Rh(III)‐catalysed arylation of quinones in 2019 [73] . The quinone substrate acted as either a C1 or C2 synthon depending on whether the 2‐arylindole substrates had a substituent at C‐3 (Scheme 40).…”
Section: Directing Group‐assisted C−h Functionalization Methodsmentioning
confidence: 99%
“…Guo et al . reported a indole‐directed Rh(III)‐catalysed arylation of quinones in 2019 [73] . The quinone substrate acted as either a C1 or C2 synthon depending on whether the 2‐arylindole substrates had a substituent at C‐3 (Scheme 40).…”
Section: Directing Group‐assisted C−h Functionalization Methodsmentioning
confidence: 99%
“…Fan, Zhang and Guo accomplished a Rh-catalysed CDC reaction of 2-arylindoles with benzoquinone for the synthesis of 9 H -dibenzo[ a,c ]carbazol-3-ol derivatives (Scheme 35). 51 Very recently, a similar reaction protocol was developed by Wang's group using the same Rh catalyst yet different bases and solvents for the same transformation. 52…”
Section: Cross-dehydrogenative Coupling Of Alkenesmentioning
confidence: 99%
“…Fan, Zhang and Guo accomplished a Rh-catalysed CDC reaction of 2-arylindoles with benzoquinone for the synthesis of 9H-dibenzo[a,c]carbazol-3-ol derivatives (Scheme 35). 51 Very recently, a similar reaction protocol was developed by Wang's group using the same Rh catalyst yet different bases and solvents for the same transformation. 52 Fan and Zhang further achieved the dehydrogenative reaction of 2-arylindazoles with maleimides for affording the indazolo[2,3-a]pyrrolo[3,4-c]quinolinones with a C-C double bond formation (Scheme 36a).…”
Section: Olefination Of Heteroarenesmentioning
confidence: 99%
“…Benzoquinone is a six‐membered ring organic compound that exhibits many interesting characters. [ 7 ] The moiety of quinone could be found in many organic compounds and could display diverse functions such as oxidant, [ 8 ] ligand, [ 9 ] promoter, [ 10 ] carbon synthon, [ 11 ] dienophile, [ 12 ] bioactivity [ 13 ] in various circumstances. Our previous works had shown that the reactions of an amido‐substituted 1,4‐quinone, N ‐(3,6‐dioxocyclohexa‐1,4‐dien‐1‐yl)acetamide ( 1a_BQ ), or N ‐(3,6‐dioxocyclohexa‐1,4‐dien‐1‐yl)propionamide ( 1b_BQ ), with NR 3 (R = Et, Pr, Bu, i‐Pentyl) in the presence of palladium salts had yielded some products with unexpected structural features (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%